Efek Variabel Kebijakan Moneter Dan Fiskal Terhadap Inflasi, Pertumbuhan Ekonomi Dan Tingkat Pengangguran Di Indonesia - Jemi Juneldi; Sri Ulfa Sentosa (Universitas Negeri Padang, 2022)
This study aims to systematize and explain the effect of monetary and fiscal Policy on inflation, economic growth and unemployment rate in Indonesia. This type of research is quantitative research, the data used is secondary data which is analyzed using VAR/VECM. The estimation results show that (1) In the long term, interest rate has negative and significant effect on inflation. In short term, interest rate has positive and significant effect on inflation. (2) Government expenditure has insignificant effect on inflation both in long and short term. (3) Interest rate has negative and significant effect on economic growth both in long and short term. (4) Government expenditure has positive effect on economic growth only significant in long term. (5) Interest rate has positive effect on unemployment rate only significant in long term. (6) Government expenditure has negative and insignificant effect on unemployment rate both in long and short term.